PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN MELALUI WORD OF MOUTH PADA PRODUK SATA - Lelly Novita Carolina; Rivera Pantro Sukma Silitonga (Human Capital Development, 2023)
This study which aims to analyze the influence of product quality and price perceptions on purchasing decisions through word of mouth on SATA products. By collecting data through distributing questionnaires to as many as 200 respondents using the purposive sampling method with the requirement of at least 2 purchases and the data was processed using structural equation modeling or SEM analysis through the Smartpls 3.0 program. It showed that product quality and price perception effect WOM and Purchasing decision directly; indirectly product quality affect purchasing decision through WOM; but indirectly price perception not significantly effect purchasing decision.